Application of the revised criteria for diagnosis and staging of Alzheimer's disease: Drug development and clinical practice - Clifford R. Jack; Ana Graf; Samantha C. Burnham; Erin G Doty; Hans J. Moebius; Philip Montenigro; Eric Siemers; Kaycee M. Sink; Leslie M. Shaw; Charlotte Thim Hansen; Kristin R. Wildsmith; Simin Mahinrad; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract The newly proposed revised criteria for diagnosis and staging of Alzheimer's disease (AD) by the Alzheimer's Association (AA) Workgroup represent a significant milestone in the field. These criteria offer objective measures for diagnosing and staging biological AD, bridging the gap between research and clinical care. Although implementation feasibility may vary across regions and settings, improving the availability and accuracy of biomarkers, especially plasma biomarkers, is expected to enhance the applicability of these criteria in clinical practice. The Fall 2023 Alzheimer's Association Research Roundtable (AARR) meeting served as a forum for gathering industry perspectives and feedback on these revised criteria, ensuring that the new criteria inform research, clinical trial design, and clinical care. In this article, we outline a summary of the newly proposed “Revised Criteria for Diagnosis and Staging of AD: AA Workgroup” and provide highlights from the AARR meeting in fall 2023. Highlights The Alzheimer's Association Research Roundtable (AARR) convened leaders from industry, academia, and government, to review the Revised Criteria for Diagnosis and Staging of AD: AA Workgroup, and gather industry perspectives and feedback on these revised criteria before its publication. The newly proposed revised criteria for diagnosis and staging of Alzheimer's disease (AD) by the AA's Workgroup represent a significant milestone, offering objective measures for the biological and staging of AD and bridging the gap between research and clinical care. Improving the availability and accuracy of biomarkers, especially blood‐based biomarkers (BBMs) is expected to improve clinical research and enhance the applicability of these criteria in clinical practice.